New high-speed steel for the cast metal-cutting tool - A. S. Chaus; М. Zhitnanski (Литьë и металлургия)
The article describes the special features of the structure and properties of cast low-alloy tungsten-free high-speed steel 11M5F in comparison with the properties of steel R6M5. There are also shown the structure and phase composition of cast carburized R6M5-based high-speed steel additionally alloyed with vanadium, titanium and niobium. There are discussed the results of microstructural analysis and mechanical tests of the cast high-speed steel in which tungsten is substituted by chromium.